Women’s Strength in the Film: An Interpersonal Analysis - Ramadhanti, Kyla Putri; Salsabila, Prina Naura; Alifia, Dinda Nabilla (Singular: Journal of Pedagogical Language, Literature, and Cultural Studies, 2024)
In this study, a woman who strives to uphold her honor and emphasizes feminism is the main subject and is shown over the course of four acts. The acts are titled "Robbery" in the first act, "The Journey" in the second, "The Confession" in the third, and "The Birth" in the fourth. The study, which is classified as a case study, employs an interpersonal approach and the theory proposed by Kress and Van Leeuwen (2006) in a qualitative descriptive technique. The results demonstrate that the visual modes complement one another, according to the researcher's findings and debate. Using an interpersonal perspective, Kress and Leeuwen's (2006) idea of drawing images can be used to describe Marlina's circumstance. The researchers also discovers that the selection and use of these modes results in a piece of art that is visually striking and successfully conveys to the viewer the content contained in the movie. This is a result of their easy-to-understand design for the broader public. According to Kress and Leeuwen's hypothesis, the following elements are dialyzed: shot, angle, position, eye contact, color meaning, multimodal, and salience.